1986
DOI: 10.1002/anie.198603531
|View full text |Cite
|
Sign up to set email alerts
|

[NbAs8]3−, a Novel Type of Complex and an Unexpected One‐Dimensional Chain Structure: [Rb{NbAs8}]2−

Abstract: which would be in agreement with the (irregular) increase in the differences A6=16(x)-6(x+ 1)1 in the series [P7 -x A~x ] 3 ~ with increasing x. It is also possible, however, that this heteroanion is unstable and decomposes into As: -and, for example, [P2Ass]37, because incorporation of the small P atom into the large As, cage is unfavorable. The "P-NMR spectra of solutions of mixtures of the pure compounds Rb3P7 and Rb3As, exhibit, even after several weeks, only the signal of P;-, so that no exchange between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
55
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 9 publications
5
55
0
1
Order By: Relevance
“…6b Combining two different main group elements within the cluster shell recently opened up a new direction, as the systems are free to adjust their charge by isolobal substitution of formal (E 14 ) 2À or (E 14 ) À by (E 15 ) AE0 . 8 According to X-ray structure analyses, ‡ both cluster anions exhibit non-deltahedral topologies (Fig. 7 In the present case, formal Ge À besides As atoms served to compensate for the high charge of an interstitial group 5 metal ion M 5+ , forming the first endohedral clusters comprising these extremely hard cations of electron-poor transition metals V and Nb.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…6b Combining two different main group elements within the cluster shell recently opened up a new direction, as the systems are free to adjust their charge by isolobal substitution of formal (E 14 ) 2À or (E 14 ) À by (E 15 ) AE0 . 8 According to X-ray structure analyses, ‡ both cluster anions exhibit non-deltahedral topologies (Fig. 7 In the present case, formal Ge À besides As atoms served to compensate for the high charge of an interstitial group 5 metal ion M 5+ , forming the first endohedral clusters comprising these extremely hard cations of electron-poor transition metals V and Nb.…”
mentioning
confidence: 67%
“…4 In conclusion, it was shown that electron-poor V and Nb atoms can be accommodated within endohedral clusters [V@Ge 8 As 4 ] 3À and [Nb@Ge 8 As 6 ] 3À , the first members of an M-Ge-As cluster family. 4 In conclusion, it was shown that electron-poor V and Nb atoms can be accommodated within endohedral clusters [V@Ge 8 As 4 ] 3À and [Nb@Ge 8 As 6 ] 3À , the first members of an M-Ge-As cluster family.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, von Schnering et al. suggested an additional π‐donation from the [As 8 ] 8− unit to the central metal, which leads to the stable 18‐electron complexes . The S 8 ‐like [Pn 8 ] 8− rings are not planar, and, hence, are not considered as aromatic.…”
Section: π‐Aromatic/antiaromatic Rings In Zintl Clustersmentioning
confidence: 99%